2012
DOI: 10.5688/ajpe76234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacists’ Participation in a Pharmacotherapy Follow-Up Program

Abstract: Objective. To evaluate the impact of a continuing pharmacy education (CPE) course on Spanish community pharmacists' participation in a pharmacotherapy follow-up program. Design. Participation in a CPE course offered 4 times over a 4-year period via satellite teleconferencing was monitored and the data analyzed to determine the course's impact on community pharmacists' participation in a pharmacotherapy follow-up program. Assessment. Community pharmacists' participation in the pharmaceutical care CPE course had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It also entails the pharmacist's involvement in activities that provide good health and prevent disease. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…It also entails the pharmacist's involvement in activities that provide good health and prevent disease. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutical Care (PC) is a professional practice where pharmacists have an active role in patient care, collaborating with other health care professionals and the patient, in order to improve patient's quality of life. 1 This professional practice is carried out through Professional Pharmacy Services (PPS), which are developing fast in the community pharmacy setting. Nevertheless, this development needs to begin during Pharmacy Degree.…”
Section: Introductionmentioning
confidence: 99%
“…Patient outcome measurements include a broad array of clinical endpoints such as smoking cessation, diet, or blood pressure in patients with hypertension, to name a few. 8,9 Specific to the pharmacy profession, studies analyzing individual CPE activities have generally, although not exclusively, shown positive effects on behaviors or patient outcomes, [10][11][12][13][14][15][16] and one systematic review cited the effectiveness of the majority of CPE programs based on their reported outcomes measures, most often knowledge or skill modification. 17 Given the frequency of evidence supporting continuing education outcomes, the ultimate CE research question is not "Is CE effective?"…”
Section: Introductionmentioning
confidence: 99%